Comparative analysis of active filters, inductor-capacitor and inductor-capacitor-inductor passive filters in reducing harmonics - Siregar, Yulianta; Azhari, Naomi; Mohamed, Nur Nabila (Institute of Advanced Engineering and Science, 2025)
Control equipment at substations requires a rectifier to convert alternative current (AC)-direct current (DC) electric current to provide DC power for relays, motors for disconnector switches and power breaker switches, and telecommunications equipment. Rectifiers have non-linear load characteristics, which can result in a waveform that is not pure sinusoidal due to the interaction of fundamental frequency sinusoidal waves with other waves known as harmonics. Therefore, to not interfere with the equipment's work, a filter is needed to reduce the harmonics produced by the rectifier. In this research, using MATLAB/Simulink, prevention was carried out using active filters, inductor-capacitor (LC), and inductor-capacitor-inductor (LCL) passive filters (Ta, Tc, and Td designs) separately. After the research was carried out, it was found that the amount of harmonics before installing the filter was 49.61%. Then, after installing the active filter, the harmonics were reduced to 0.29%, the installation of the passive LC filter was reduced to 9.29%, and the installation of the LCL filter (Ta, Tc, and Td) became 1.44%, 0.29%, and 1.44%.